Edukasi Pentingnya Kebersihan Diri Selama Menstruasi pada Remaja Putri di Ma’had Tahfidz Al-Quran At-Tazkiyah Cibinong Bogor: Education on the Importance of Personal Hygiene During Menstruation for Young Women at the Ma’had Tahfidz Al-Quran At-Tazkiyah Cibinong Bogor - Suminar, Ari; Gunarmi, Gunarmi; Ismawati, Riska (J.Abdimas: Community Health, 2025)
Personal Hygiene is an action taken to maintain physical and psychological well-being through health and cleanliness. Personal hygiene during menstruation can be done by maintaining the health of reproductive organs during menstruation. Self-care during menstruation is important to maintain cleanliness and prevent infection. The benefits of personal hygiene during menstruation are to prevent infection, reduce odor, help stay comfortable, improve health and increase self-confidence. If you do not maintain personal hygiene during menstruation, it can cause serious health risks such as urinary tract infections, reproductive tract infections, skin irritation, infertility and other complications. The purpose of personal hygiene during menstruation is to improve health, maintain personal health, prevent disease and increase self-confidence during menstruation. The method used in providing health education in carrying out personal hygiene during menstruation at the Ma'had tahfidz al-quran At-Tazkiyah, Cibinong District - Bogor Regency is by using animated video media and ending with a question and answer session. The results of providing health education on personal hygiene during menstruation, after providing education related to the importance of personal hygiene during menstruation, all female students at the Ma'had Tahfidz al-Quran At-Tazkiyah have understood what personal hygiene is, the purpose of personal hygiene during menstruation, personal hygiene behavior during menstruation, forms of personal hygiene during menstruation and the impacts that occur if personal hygiene is not carried out during menstruation. Before this material was provided, female students still did not understand the importance of personal hygiene during menstruation. Keywords : Menstruation, Personal Hygiene, Teenage girls,